2008
DOI: 10.1002/gps.2075
|View full text |Cite
|
Sign up to set email alerts
|

Late and very‐late first‐contact schizophrenia and the risk of dementia–a nationwide register based study

Abstract: schizophrenic patients with late- and very-late first-contact with the psychiatric hospital system are at two to three times higher risk of subsequently getting a diagnosis of dementia compared to patients with osteoarthritis and compared to the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 14 publications
(25 reference statements)
2
79
1
Order By: Relevance
“…Similarly, the debate on whether early-life or late-life depression is more important risk factor is ongoing (3,6,(8)(9)(10)(11)(12)(13). The results of studies investigating the association between bipolar disorder and dementia (14)(15)(16)(17) and late-life schizophrenia and dementia (18)(19)(20)(21) have been equally heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the debate on whether early-life or late-life depression is more important risk factor is ongoing (3,6,(8)(9)(10)(11)(12)(13). The results of studies investigating the association between bipolar disorder and dementia (14)(15)(16)(17) and late-life schizophrenia and dementia (18)(19)(20)(21) have been equally heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…after age 40 years) were at increased risk of dementia [20-22]. The Danish study reported a 2.4-fold increased risk of dementia after almost 5-years of follow-up in 1,206 late-onset schizophrenia patients when compared to normal controls [20].…”
Section: Introductionmentioning
confidence: 99%
“…33 In Danish register data study, patients with late-onset schizophrenia (first-contact over age 40) and very-late-onset schizophrenia (first contact over age 60) were both 3-times more likely to develop dementia than patients with osteoarthritis, and twice more likely to develop dementia than a gender-and age-matched sample of the general population over a median follow-up period of 3-4 years. 61 Another study, based on the same registry approach, showed that patients with very-lateonset delusional disorder were 8-times more likely to develop dementia (15.2% versus 2.1%) compared to those with osteoarthritis over a median follow-up period of approximately 2 and 4 years, respectively. 60 Compared to age-, gender-, and calendar-matched general population, very-late-onset delusional disorder were 5-times more likely to develop dementia.…”
Section: Is Late-onset Psychosis a Prodromal Symptom Of Dementia?mentioning
confidence: 99%
“…A certain cutoff Mini-Mental State Examination (MMSE) score or similar neuropsychological test score for inclusion used in many studies have not been strictly comparable. Some studies excluded patients only on the basis of a clinical diagnosis of dementia, 58,60,61,97 while another study did not use any specific exclusion criteria regarding cognitive status. 46 Considering the lack of standardized and validated study design, it is not surprising that cognitive cut-off scores adopted in study populations varied from a MMSE score of 17.6 46 to 28.21.…”
Section: Is Late-onset Psychosis a Prodromal Symptom Of Dementia?mentioning
confidence: 99%